Safety and efficacy of ozanimod versus interferon beta-1a in relapsing multiple sclerosis (SUNBEAM): a multicentre, randomised, minimum 12-month, phase 3 trial - Comi, Giancarlo; Kappos, Ludwig; Selmaj, Krzysztof W; Bar-Or, Amit; Arnold, Douglas L; Steinman, Lawrence; Hartung, Hans-Peter; Montalban, Xavier; Kubala Havrdová, Eva; Cree, Bruce A C; Sheffield, James K; Minton, Neil; et al. (The Lancet. Neurology, 2019)
BACKGROUND: Ozanimod, a sphingosine 1-phosphate receptor modulator, selectively binds to receptor subtypes 1 and 5 with high affinity. The RADIANCE phase 2 study showed that ozanimod had better efficacy than placebo on MRI measures, with a favourable safety profile, in participants with relapsing multiple sclerosis. The SUNBEAM study aimed to assess the safety and efficacy of ozanimod versus intramuscular interferon beta-1a in participants with relapsing multiple sclerosis. METHODS: SUNBEAM was a randomised, double-blind, double-dummy, active-controlled phase 3 trial done at 152 academic medical centres and clinical practices in 20 countries. We enrolled participants aged 18-55 years with relapsing multiple sclerosis, baseline expanded disability status scale (EDSS) score of 0·0-5·0, and either at least one relapse within the 12 months before screening or at least one relapse within 24 months plus at least one gadolinium-enhancing lesion within 12 months before screening. Participants were randomly assigned 1:1:1 by a blocked algorithm stratified by country and baseline EDSS score to at least 12 months treatment of either once-daily oral ozanimod 1·0 mg or 0·5 mg or weekly intramuscular interferon beta-1a 30 μg. Participants, investigators, and study staff were masked to treatment assignment. The primary endpoint was annualised relapse rate (ARR) during the treatment period and was assessed in the intention-to-treat population. Safety was assessed in all participants according to the highest dose of ozanimod received. This trial is registered at ClinicalTrials.gov, number NCT02294058 and EudraCT, number 2014-002320-27. FINDINGS: Between Dec 18, 2014, and Nov 12, 2015, 1346 participants were enrolled and randomly assigned to ozanimod 1·0 mg (n=447), ozanimod 0·5 mg (n=451), or interferon beta-1a (n=448). 91 (6·8%) participants discontinued the study drug (29 in the ozanimod 1·0 mg group; 26 in the ozanimod 0·5 mg group; and 36 in the interferon beta-1a group). Adjusted ARRs were 0·35 (0·28-0·44) for interferon beta-1a, 0·18 (95% CI 0·14-0·24) for ozanimod 1·0 mg (rate ratio [RR] of 0·52 [0·41-0·66] vs interferon beta-1a; p<0·0001), and 0·24 (0·19-0·31) for ozanimod 0·5 mg (RR 0·69 [0·55-0·86] vs interferon beta-1a; p=0·0013). Few ozanimod-treated participants discontinued treatment because of adverse events (13 [2·9%] who received ozanimod 1·0 mg; seven [1·5%] who received ozanimod 0·5 mg; and 16 [3·6%] who received interferon beta-1a). No first-dose, clinically significant bradycardia or second-degree or third-degree atrioventricular block was reported. The incidence of serious adverse events was low and similar across treatment groups (13 [2·9%] participants who received ozanimod 1·0 mg; 16 [3·5%] who received ozanimod 0·5 mg; and 11 [2·5%] who received interferon beta-1a). No serious opportunistic infections occurred in ozanimod-treated participants. INTERPRETATION: In participants with relapsing multiple sclerosis treated for at least 12 months, ozanimod was well tolerated and demonstrated a significantly lower relapse rate than interferon beta-1a. These findings provide support for ozanimod as an oral therapy for individuals with relapsing multiple sclerosis. FUNDING: Celgene International II.
Keywords: Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; neurozobrazování; velikost orgánu; Humans; lidé středního věku; indany; Disease Progression; Quality of Life; Female; oxadiazoly; dospělí; Indans; lidé; receptory sfingosin-1-fosfátu; bradykardie; Sphingosine-1-Phosphate Receptors; kvalita života; imunosupresiva; Adult; Immunosuppressive Agents; Cognition Disorders; Bradycardia; Gray Matter; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; Oxadiazoles; stupeň závažnosti nemoci; Male; Middle Aged; Brain; atrioventrikulární blokáda; šedá hmota; Atrioventricular Block; Severity of Illness Index; Neuroimaging; progrese nemoci; kognitivní poruchy; Organ Size; mužské pohlaví; Interferon beta-1a; interferon beta 1a